Effects of Corm Dipping in Salicylic Acid or Potassium Nitrate on Growth, Flowering, and Quality of Saffron - Khayyat Mehdi; Jabbari Mani; Fallahi Hamid-Reza; Samadzadeh Alireza (Journal of Horticultural Research, 2018)
The present research was conducted to find influence of salicylic acid (SA) at 0.5, 1, and 2 mM and potassium nitrate (KNO3) at 250, 500, and 1 000 ppm on reproductive and vegetative parameters, and color characteristics of saffron under field condition. The results indicated the highest a, L, and chroma and the lowest b at 2 mM SA treatment. The highest flowering appearance rate and membrane stability index and the lowest electrolyte leakage were observed at 2 mM SA and to lesser extent at 1000 ppm KNO3. The highest flower number, corolla dry weight, and stigma dry weight was shown in plants treated with SA. Chlorophyll a content and Fv/Fm value increased with the application of 2 mM SA. The data indicated the effectiveness of SA on the growth of saffron.